Fathers of the Nation: Barack Obama Addresses Nelson Mandela (Altre Modernità, 2014)
This essay analyzes Barack Obama’s Nelson Mandela Memorial speech together with other seminal texts of Obama’s political and personal creed, such as his book Dreams from My Father (1995) and his speech “A More Perfect Union” (2008). This reading becomes helpful to understand Mandela’s transnational power, which Obama uses to comment on the United States by comparing Madiba to other American “fathers of the nation.” Thus, he uproots Mandela’s from a specifically South African legacy, expands his figure, and addresses him as a transnational father of his own nation, whose power, influence, and example transcend South African borders. As a consequence of this enlargement and transnational validation of Mandela’s figure, the speech delivered at the Memorial becomes an occasion to tackle American past and future, while the memory of Madiba and his driving example in Obama’s life serve to reinforce previous positions conveyed in other discourses by the American President, such as the “A More Perfect Union” speech delivered in Philadelphia in 2008.
Keywords: Barack Obama; Nelson Mandela; genealogy; nationhood